Educational Management Operations Research in Broadcasting: A SITOREM-Based Strategy for Training Optimization - Sifak Sifak; Soewarto Hardhienata; Dian Wulandari (JURNAL AL-TANZIM, 2026)
This study aims to formulate priority strategies to improve the effectiveness of education and training in the production and broadcasting sector at a television station using the Scientific Identification Theory to Conduct Operation Research in Education Management (SITOREM) approach. The study used a quantitative descriptive method involving 164 employees selected through quota sampling from a population of 278 employees at 30 TVRI stations in Indonesia. Data were collected using a questionnaire measuring the effectiveness of education and training, competency development, transformational leadership, and communication and information technology literacy. Data analysis was conducted using path analysis and SITOREM analysis. The results showed that communication technology literacy had the strongest direct influence on the effectiveness of education and training (β = 0.472), followed by transformational leadership (β = 0.182), information technology literacy (β = 0.150), and competency development (β = 0.137). The SITOREM analysis identified 14 priority improvement indicators across communication, data management, evaluation, leadership, integration of learning technology, competency development, and optimisation of training results. Research findings show that strengthening technological literacy, transformational leadership, and competency development are key strategies in increasing the effectiveness of education and training and supporting digital transformation.